Legal Analysis of Sharenting Practices in the Digital Era: Implications for Children's Privacy Rights in Indonesia - Putri, Shopie Hana; Heriamariaty, Heriamariaty; Jalianery, Joanita (Journal of Law, Politic and Humanities, 2025)
Sharenting is the practice of parents sharing children's activities on social media, has become a popular phenomenon in the digital era. Although this practice is often performed to demonstrate parenting abilities, sharenting has the potential to violate children's privacy rights and pose a risk of exploitation, kidnapping and misuse of personal data. This research aims to analyze the related legal gaps sharenting in Indonesia, as well as recommending policies to increase protection of children's privacy rights. The research method used is normative legal research, with a focus on analysis of statutory regulations and related literature sharenting. The research results show that although Indonesia has several regulations that protect children's rights, such as the Child Protection Law, Personal Data Protection Law, and Human Rights Law. There are no specific rules governing sharenting practices. Therefore, it is necessary to revise existing laws, increase public awareness about the dangers of the practice sharenting towards children, as well as the active role of institutions such as the Indonesian Child Protection Commission (KPAI) to protect children's privacy rights on social media. Thus, this research recommends concrete steps to create a safe environment for children in the digital era